The Relationship Between the Quality of Hemodialysis Services and Family Support on the Quality of Life of Patients with Chronic Kidney Failure at Hermina Daan Mogot Hospital - Silviyah, Syifa; Lestari, Nurmala Dewi Ria; Aziz , Abdul (IJBLE Scientific Publications Community Inc., 2025)
Chronic kidney disease is a global health problem that impacts the quality of life of patients, especially those undergoing long-term hemodialysis. This Therapy not only imposes physical burdens but also impacts the psychological, social, and environmental aspects of patients. Therefore, quality healthcare and family support are crucial to improving their quality of life. The purpose of this study was to analyze the relationship between hemodialysis service quality and family support with the quality of life of chronic kidney disease patients at Hermina Daan Mogot Hospital. This study employed a cross-sectional analytical method, involving 110 hemodialysis patients selected using a purposive sampling technique. Data were collected through a structured questionnaire that covered service quality, family support, and quality of life, based on the four WHOQOL-BREF domains (physical, psychological, social, and environmental). Data were then analyzed using correlation and multiple linear regression. The results showed that hemodialysis service quality had a significant positive relationship with patient quality of life (p < 0.05), as did family support (p < 0.05). Simultaneous analysis showed that both variables together contributed significantly to improving quality of life. Conclusion: Improving service quality (technical aspects, facilities, and interactions) and family support (emotional, informational, and instrumental) are crucial. Recommendations include developing service standards, training in caring behavior for nurses, and family education programs to optimally improve the quality of life of chronic kidney disease patients.